Ethnic Fractionalization and Polarization in New Capital City of Nusantara, Indonesia: Analysis of Potential Conflict - Gunawan, I Ketut; Taufik, Mohammad; Somlai, Iván Győző (Universitas Muhammadiyah Yogyakarta, 2024)
This study analyzes ethnic fractionalization and polarization in the new Indonesian Capital of Nusantara (IKN), with a focus on the potential for ethnic conflict as the government directs significant resources towards its development. Data was collected from 54 villages within IKN territory over five months and analyzed quantitatively. The findings show a high ethnic fractionalization index of 0.79 and a slightly high polarization index of 0.61, indicating a moderate risk of conflict. However, the ethno-demographic and ethnopolitical conditions remain conducive to supporting IKN's development. While previous research has addressed ethnic conflict in Indonesia, few studies have examined its implications for major national projects like IKN's development. This study offers a new quantitative perspective on how ethnic diversity influences large-scale governmental projects, highlighting the role of ethnic fractionalization and polarization in shaping the stability of IKN's development. Although such a polarization index indicates the potential for conflict being slightly high, the ethno-demographic and ethnopolitical condition in IKN is still relatively conducive to providing supporting capacity to IKN development, viewed from a statistical and ethnopolitical perspective.